Effect of Practical Delivery-nursing Simulation Education on Team-based Learning on the Nursing Knowledge, Self-efficacy, and Clinical Competence of Nursing Students - Sun Hee Lee (Korean Society of Women Health Nursing, 2018)
PURPOSE: To identify the effects of delivery-nursing simulation education using team-based learning on the delivery nursing knowledge, self-efficacy, and clinical competence of nursing students. METHODS: The study used a nonequivalent, control group, quasi-experimental design. The team-based learning was applied to the experimental group, while the individual learning was applied to the control group. Data were collected from October 12 to December 7, 2016, and analyzed using the SPSS/WIN 22.0 program. RESULTS: Comparison between the experimental and control group showed no significant difference in delivery-nursing knowledge (t=−0.33, p=.741) or self-efficacy (t=−0.65, p=.515). However, a significant difference (t=−2.09, p=.048) in the nursing-skills aspect of clinical competence was found between the experimental and control groups after the practical simulation education. CONCLUSION: Delivery-nursing simulation education using team-based learning was more effective in improving the nursing-skills aspect of nursing competence than was delivery-nursing simulation education based on individual learning.